Հարկային համակարգը Երևանի խանության տարածքում 16-17-րդ դարերում - Արթուր Հակոբյան (ՀՀ ԳԱԱ հրատ.)
In 16th century Eastern Armenia came under the Safavid dominance. Yerevan became the center of the newly formed Yerevan Khanate. In 16-17 centuries Armenians, being the main part of the Yerevan Khanate’s overall population, were heavily suffering from the Ottoman-Persian wars. Besides, Armenians were imposed various sorts of heavy taxes and dues. The main taxes, dues and the whole taxation system of the Yerevan Khanate are comprehensively analysed in this article.
Keywords: Social Sciences; Revenue; Taxation; Internal Revenue